2011
DOI: 10.1111/j.1467-9957.2009.02159.x
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Non-Linearities and Market Efficiency in the Mexican Stock Market

Abstract: We investigate the weak form of the efficient capital market hypothesis through the detection of a non-linear dynamic with potential for predictability of stock returns in the Mexican stock market. We apply the Hinich portmanteau bicorrelation test and the Brock, Dechert and Scheinkman test to the data. We observe that all the return series are characterized by a few brief periods of highly significant non-linearity. However, we cannot say that the Mexican market fails to satisfy the weak form of the efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Hinich and Patterson (1985) apply a test can distinguish between white noise and purely random noise to return of 15 common stocks and conclude that these daily stock returns are produced by a nonlinear process. Mexico has also been analyzed in terms of being weak-form efficient by Bonilla, et al (2011) who find that all of the return series are characterized by a few periods with highly significant non-linearity.…”
Section: Background and Relevant Literaturementioning
confidence: 99%
“…Hinich and Patterson (1985) apply a test can distinguish between white noise and purely random noise to return of 15 common stocks and conclude that these daily stock returns are produced by a nonlinear process. Mexico has also been analyzed in terms of being weak-form efficient by Bonilla, et al (2011) who find that all of the return series are characterized by a few periods with highly significant non-linearity.…”
Section: Background and Relevant Literaturementioning
confidence: 99%
“…Many studies have reported nonlinear behavior in different financial assets series all around the world, such as stocks, currencies, bonds and commodities, and with several time frames. For example, in North America (Hinich and Patterson, 1985;Scheinkman and LeBaron, 1989;Hsieh, 1991;Brock et al, 1996); in European markets (Abhyankar et al, 1995;Opong et al, 1999;Kosfeld and Robé, 2001;Todea and Zoicas-Ienciu, 2008); in Asian markets (Ammermann and Patterson, 2003;Lim and Hinich, 2005); and in Latin American markets (Bonilla et al, 2006;Bonilla et al, 2008;Bonilla et al, 2010;Bonilla et al, 2011;Espinosa et al, 2013).…”
Section: Intoducciónmentioning
confidence: 99%